Runaway current suppression by secondary massive gas injection during the disruption mitigation phase on J-TEXT. (17th June 2019) - Wei, Y N; Yan, W; Chen, Z Y; Tong, R H; Jiang, Z H; Yang, Z J
Abstract: Disruption is one of the urgent problems for future tokamaks in possibly causing heat loads, halo currents, and runaway electrons (REs). Massive impurity injection is a feasible way to mitigate the disruption. Due to the limit of the impurity injection rate and the assimilation efficiency, single injection of impurity may not be sufficient to totally suppress RE generation in future large-scale devices. Large number of REs can form runaway currents and carry a large current fraction in the plasma current. In order to suppress the formation of the runaway current, a secondary gas injection from an additional valve with a delay time to the valve of the disruption mitigation system is performed on J-TEXT. When the additional high-Z impurity gas arrives at the plasma edge before the thermal quench, the runaway current can be significantly suppressed by weakening the primary RE generation. The final formed runaway current can be reduced by 90% in this way. When the additional high-Z impurity gas arrives at the plasma edge during the current quench, the runaway current can be partially suppressed by weakening the avalanche RE generation. The final formed runaway current can be reduced by 40%–80% in this way.